Fitness lunch bag: the ability to keep foods cold and out of the danger zone - Wong, Kerrilyn; BCIT School of Health Sciences, Environmental Health; Heacock, Helen (BCIT Environmental Public Health Journal, 2014)
Background: Improper storage of food is one of the top ten food handling practices that cause a foodborne illness. This study assessed whether the Fitness Lunch Bag was able to keep precooked chicken breast cold at below 4°C (40°F) for 8 hours and to determine if the layers of the bag kept food consistent at the same temperature. Methods: Three SmartButtons, continuous temperature data logging devices, were inserted into three precooked and chilled chicken breasts. The three chicken breasts were placed within three trays inside the Fitness Lunch Bag that remained at room temperature for 8 hours. The internal temperatures were logged at one hour intervals. A total of 30 samples were collected. NCSS was used for statistical analysis of the data by regression/correlation and ANOVA. Results: The Fitness Lunch Bag was unable to hold cold food safely, at 4°C (40°F) and below for 8 hours. All three layers were found to exceed 4°C (40°F) within the first hour (p-value of 0.000 by 1 sample t-test). In addition, all three layers of the Fitness Lunch Bag were found to not be equivalent in retaining a consistent temperature throughout the bag (p-value of 0.000000 < 0.05 by regression analysis at the 8 hour mark). Layer 2 was the best at retaining the lowest temperature for the chicken breasts, followed by layer 1. Moreover, layer 3 was found to display the warmest temperatures out of the three layers. Conclusion: The results of the study show that the Fitness Lunch Bag does not have the ability to keep cold foods out of the danger zone, 4-60°C (40 – 140°F), for 8 hours. In addition, the bag was not capable of keeping cold foods safe at the 1 hour mark. Caution should be used with any type of lunch bag, insulated and/or frozen gel packed, especially with the potentially hazardous foods.